MOLAR INCISOR HYPOMINERALIZATION (MIH) – THERAPEUTIC OPTIONS FOR THE FIRST PERMANENT MOLARS - Olimpia Bunta; Mihaela Salceanu; Mircea Ghergie; Mihaela Pastrav; Dana Festila (Romanian Journal of Oral Rehabilitation)
Molar-incisor hypomineralization (MIH) is a highly prevalent dental pathology in young children, which affects primarily the first permanent molars and the permanent incisors. Being a developmental defect, its’ treatment must take into consideration multiple aspects like extensionand size of defect, structures affected, caries involvement, sensitivity and patient compliance and cooperation. The general recommendations imply using minimally invasive procedures that aim to protect, strengthen and preserve dental structures. As treatment options for MIH affected molars vary with case severity, all available therapeutic options from prevention to extraction must be taken into consideration in this decision making. This paper presents the documented therapeutic options of the MIH affected molars.